Grants to needy countries? A study of aid composition between 1975 and 2005 - Pernilla Johansson (Lund University, School of Economics and Management, Department of Economics, 2009)
This paper studies whether the poorest and most indebted countries receive aid in the form of grants rather than loans. By studying bilateral aid flows to low- and middle-income countries between 1975 and 2005, the paper provides evidence on the determinants of the grant component of aid flows. While the empirical analysis finds no evidence that more indebted countries receive a higher grant component, it shows that poorer countries receive a significantly higher grant component of aid, although the size of the effect is rather limited.
Keywords: F34; F35; 330; Aid composition; Aid allocation; Indebtedness; Poverty